What a Museum Cannot Bear Witness To: Bursa City Museum and the Representation of the Jewish Minority. Issue 1 (1st July 2021) - Eklemezler, Sercan
Abstract: The primary motivation behind this study is assessing how successful "inclusive" urban museums really are in representing ethnic/religious minorities. The research site is Bursa City Museum, Turkey, where the Bursa Jewish Community used to be one of the key social and cultural elements of the city. In-depth interviews are the main method of study, since the opinions of this minority on the subject are the main focus. The main aim here is to reveal the ideas of the community (whose collective memories are threatened with extinction) about being represented in the museum, and from this analysis to make constructive suggestions for the institution. It seems that the community cares about being identified as part of the city, but is indifferent to the institution of the museum, partly due to problems in the ways in which they are represented.